A room temperature continuous-wave nanolaser using colloidal quantum wells - Zhili Yang (Nature Portfolio, 2017)
Colloidal nanocrystals are a promising material for easy-to-fabricate nanolasers, but suffer from high threshold powers. Here, the authors combine colloidal quantum wells with a photonic-crystal cavity into a stable, continuous-wave room-temperature nanolaser with a threshold below one microwatt